2020
DOI: 10.3892/etm.2020.8806
|View full text |Cite
|
Sign up to set email alerts
|

Distress in neurocognitive disorders due to Alzheimer's disease and stroke

Abstract: Patients with neurocognitive disorders experience subjectively the concept of quality of life; this is the reason why researchers avoid approaching this concept and prefer to focus attention on the emotional profile of the caregivers. Many studies highlight the efforts both emotional and financial made by caregivers in case of patients diagnosed with neurocognitive disorders. The present study shows the differences between the patients diagnosed with neurocognitive disorder due to Alzheimer's disease and patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…However, the exact pathogenesis is still elusive. In recent years, many theories have been proposed, including the monoamine theory, dysfunction in hypothalamus-pituitary-adrenal (HPA) axis hypothesis, and neurotrophic theory inflammatory theory [64][65][66][67]. Studies demonstrated that immune system activation played a major role in the development of depression [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact pathogenesis is still elusive. In recent years, many theories have been proposed, including the monoamine theory, dysfunction in hypothalamus-pituitary-adrenal (HPA) axis hypothesis, and neurotrophic theory inflammatory theory [64][65][66][67]. Studies demonstrated that immune system activation played a major role in the development of depression [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…While AD cannot be cured and there is no way to stop or slow its progression at the moment, our approach offers the possibility of treating symptoms several years before they begin to appear [ 4 , 99 , 100 ] under an individually tailored biomarker scheme rather, than using a one-size-fits-all population average strategy [ 99 , 100 , 101 ], while taking individual variability into account. Although our results can certainly be used to move AD research in this direction, it is also important to consider the legal implications and the preparation that health providers, neurologists, and centers specializing in AD and neurodegeneration must have in order to interpret these findings and provide proper counseling to patients and their families [ 102 , 103 , 104 ]. Another challenge in the years to come is also to significantly reduce the misinformed conclusions produced by ML methods in the absence of clinical domain expertise [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…These disease severity indexes include-besides clinical data-also a scoring of the patient's overall health status, including his or her own perception of well-being. While the psychological impact and particularly patients' perception of well-being appears to be a less investigated area, principally because of its subjective component, recent research has been highlighting the importance of investigating this concept as well, through the use of quantifiable methodological parameters, with the aim to assist in the development of therapeutic interventions that are more comprehensively adapted to patients' needs [113].…”
Section: Additional Remarks For Potential Consideration In Future Researchmentioning
confidence: 99%